Ethnological: Indian Villages at the Minnesota State Fair, 1920-1945 - Szydel, Sean (My University, 2014)
Geographically located in Saint Paul near Hamline, the Minnesota State Fair is a place for education, fun, and family. Agriculture is the main attraction and remains the constant reason why the Minnesota State Fair is still in existence and remains popular today. However, there is a side to the fair that has not be discussed in rich detail by many authors and that is the existence and social/cultural impact of Indian Villages starting in 1894. Minnesota participated in the 1893 Columbian Exposition geographically located in Chicago, Illinois. The idea came from Indians playing Lacrosse in the Indian Village at the Columbian Exposition and that sparked the discussion and implementation of an Indian Village as an educational experience for the bourgeois fairgoer. As World Exhibitions and Fairs displayed Indian Villages as progress of western civilization, the Minnesota State Fair also displayed these same type of ideologies in terms of human progress, Colonialism, Enlightenment, and Social Darwinism.
Keywords: Colonialism; Indian Village; Minnesota State Fair